Reactivity of ethyl nitrosoacrylate toward pyrrole, indole and pyrrolo[3,2-c]carbazole: an experimental and theoretical study - Benzi, Alice; Lopes, Susana M. M.; Nunes, Sandra C. C.; Giorgi, Gianluca; Bianchi, Lara; Tavani, Cinzia; Pais, Alberto A. C. C.; Petrillo, Giovanni; Pinho e Melo, Teresa M. V. D. (Frontiers in Chemistry, 2023)
Nitrosoalkenes react with 8-methyl-1,6-dihydropyrrolo[3,2-c]carbazole to give both 2- and 3-alkylated products via hetero-Diels-Alder reaction followed by the cycloadduct ring-opening. Quantum chemical calculations, at DFT level of theory, were carried out to investigate the regioselectivity of the cycloaddition of ethyl nitrosoacrylate with 1,6-dihydropyrrolo[3,2-c]carbazoles as well as with pyrrole and indole, allowing a more comprehensive analysis of the reactivity pattern of nitrosoalkenes with five-membered heterocycles. Furthermore, theoretical calculations confirmed that ethyl nitrosoacrylate reacts with these heterocycles via a LUMOheterodiene-HOMOdienophile controlled cycloaddition. The reactivity of one of the oxime-functionalized 1,6-dihydropyrrolo[3,2-c]carbazole was explored and a new hexahydropyrido[4′,3':4,5]pyrrolo[3,2-c]carbazole system was obtained in high yield via a one-pot, two-step procedure.